Islam dan Budaya Lokal: Kajian terhadap Interelasi Islam dan Budaya Sunda - Sumpena, Deden (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2012)
This paper will try to outline a conceptual framework of Islam and the struggle in the realm of Tatar Sunda. For the Sundanese peole, Islam has become an integral part. This study also will explore the feasibility of Islamic Tatar Sunda regarded as a sect of so many schools, both of which have been or will be born and grow that to this day still survive in parts of the world community. Since the earliest historical experience, Sundanese people always put the values of Islam in a very central position in whole aspects of life. Phenomena contained in the philosophy of life, the Sundanese are reflected in the expression of Silih Asah, Silih Asih, Silih Asuh really is one of the principle of life is colored by the spirit of Islamic teachings.